Choroidal melanoma with synchronous Fuchs’ adenoma and novel ATRX mutation - Elli Harford; Jane M. Palmer; William J. Glasson; Sunil K. Warrier; Kevin J. Whitehead; Kelly M. Brooks; Peter A. Johansson; Nicholas K. Hayward; Lindsay A. McGrath (International Journal of Retina and Vitreous, 2022)
Abstract Background To report a case of Fuchs’ adenoma occurring in an eye with a large choroidal melanoma. We have reviewed the literature to describe the clinical presentation, ultrasound characteristics and pathological features of these entities. Case presentation A 69-year-old Caucasian man presented with vision loss from a large choroidal melanoma. Enucleation showed an incidental Fuchs’ adenoma in the same eye. Whole-exome sequence analysis was also performed on the patient’s blood and melanoma, which showed a rarely-reported ATRX mutation. Conclusions Fuchs’ adenoma is an under-diagnosed benign age-related hyperplasia of the non-pigmented ciliary epithelium (NPCE). Given its location and characteristics, it can be mistaken for choroidal melanoma and clinicians are reminded how to differentiate between these pathologies and that they may co-exist.